Efficacy and safety of larotrectinib in TRK fusion-positive primary central nervous system tumors. Issue 6 (27th November 2021) - Doz, François; van Tilburg, Cornelis M; Geoerger, Birgit; Højgaard, Martin; Øra, Ingrid; Boni, Valentina; Capra, Michael; Chisholm, Julia; Chung, Hyun Cheol; DuBois, Steven G; Gallego-Melcon, Soledad; Gerber, Nicolas U; et al.
Abstract: Background: Larotrectinib is a first-in-class, highly selective tropomyosin receptor kinase (TRK) inhibitor approved to treat adult and pediatric patients with TRK fusion-positive cancer. The aim of this study was to evaluate the efficacy and safety of larotrectinib in patients with TRK fusion-positive primary central nervous system (CNS) tumors. Methods: Patients with TRK fusion-positive primary CNS tumors from two clinical trials (NCT02637687, NCT02576431) were identified. The primary endpoint was investigator-assessed objective response rate (ORR). Results: As of July 2020, 33 patients with TRK fusion-positive CNS tumors were identified (median age: 8.9 years; range: 1.3–79.0). The most common histologies were high-grade glioma (HGG; n = 19) and low-grade glioma (LGG; n = 8). ORR was 30% (95% confidence interval [CI]: 16–49) for all patients. The 24-week disease control rate was 73% (95% CI: 54–87). Twenty-three of 28 patients (82%) with measurable disease had tumor shrinkage. The 12-month rates for duration of response, progression-free survival, and overall survival were 75% (95% CI: 45–100), 56% (95% CI: 38–74), and 85% (95% CI: 71–99), respectively. Median time to response was 1.9 months (range 1.0–3.8 months). Duration of treatment ranged from 1.2–31.3+ months. Treatment-related adverse events were reported for 20 patients, with grade 3–4 in 3 patients. No new safety signals were identified. Conclusions: In patients with TRK fusion-positive CNS tumors, larotrectinib demonstrated rapid and durable responses, high disease control rate, and a favorable safety profile.